Clinical effect and mechanism of aerobic exercise for knee osteoarthritis: a mini review - Hu, Hao-Yu; Jia, Lu-Ning; Zhao, Wen-Yu; Guo, Sheng-Jie; Fang, Zhi-Min; Li, Xi-Yue; Zheng, Yi-Li; Chen, Pei-Jie (Frontiers in Physiology, 2025)
Knee osteoarthritis (KOA) is a prevalent degenerative joint disease characterized by pain, dysfunction, and stiffness, significantly impairing quality of life. While various interventions exist, aerobic exercise stands out as a safe and effective core treatment. This review synthesizes current evidence on the therapeutic benefits and underlying mechanisms of aerobic exercise for KOA. We recommend low-to-moderate intensity aerobic training (RPE 11–14) for KOA patients, performed 3–4 times per week for 30–60 min, for at least 6 weeks. Recommended modalities include gentle exercises like Wuqinxi, Baduanjin, and yoga, or water-based exercises and swimming, which can offer additional benefits for weight management. The therapeutic effects of aerobic exercise on KOA are multifaceted. Mechanistically, it modulates inflammatory responses by balancing pro- and anti-osteoclastogenic cytokines and inhibiting inflammatory signaling pathways, thereby alleviating pain and promoting cartilage repair. Additionally, aerobic exercise contributes to weight control, reducing knee joint load and improving cartilage health. It also provides appropriate mechanical loading to facilitate osteogenesis and preserves muscle mass, particularly in the lower extremities, mitigating muscle loss and reducing joint pressure. Despite these benefits, the precise exercise modalities, patterns, and intensities for different KOA grades remain to be fully defined and require further clinical validation. Future research should focus on quantifying exercise prescriptions to optimize anti-inflammatory effects, muscle preservation, and cartilage regeneration, as well as exploring the potential of combining aerobic exercise with other training types to enhance outcomes.